2006
DOI: 10.1074/jbc.m603085200
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of the Complement Control Protein Homolog of Herpesvirus Saimiri

Abstract: Herpesvirus saimiri (HVS) is a lymphotropic virus that causes T-cell lymphomas in New World primates. It encodes a structural homolog of complement control proteins named complement control protein homolog (CCPH). Previously, CCPH has been shown to inhibit C3d deposition on target cells exposed to complement. Here we have studied the mechanism by which it inactivates complement. We have expressed the soluble form of CCPH in Escherichia coli, purified to homogeneity and compared its activity to vaccinia virus c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…It is worth noting that RCP-1 showed the strongest binding to C4b, out of all proteins tested, likely directly related to its doubled binding sites and superior decay accelerating activity. Surprisingly, RCP-1 was also highly effective in accelerating decay of the alternative C3 convertase, which makes it fairly unique among the viral complement inhibitors; the activity of KCP and RCP-H was negligible, and previous reports have only shown very weak alternative DAA for VCP and complement control protein homolog (CCPH) encoded by herpesvirus saimiri (33). However, the lower activity observed for the CCP5-8 portion suggests that the naturally occurring shorter isoform for strain 17577 (19) would be less effective than the full-length RCP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that RCP-1 showed the strongest binding to C4b, out of all proteins tested, likely directly related to its doubled binding sites and superior decay accelerating activity. Surprisingly, RCP-1 was also highly effective in accelerating decay of the alternative C3 convertase, which makes it fairly unique among the viral complement inhibitors; the activity of KCP and RCP-H was negligible, and previous reports have only shown very weak alternative DAA for VCP and complement control protein homolog (CCPH) encoded by herpesvirus saimiri (33). However, the lower activity observed for the CCP5-8 portion suggests that the naturally occurring shorter isoform for strain 17577 (19) would be less effective than the full-length RCP.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing KCP and RCP with other viral complement inhibitors such as VCP, CCPH (33), and smallpox inhibitor of complement enzymes (38), which all consist of four CCP domains, some similarities can be found as follows: (i) all of them act as cofactors for C3b and C4b cleavage by FI; (ii) all but RCP-1 exhibit decay acceleration activity for the classical pathway that is much stronger than that for the alternative pathway (if such activity can at all be detected); and (iii) inhibitors with a single binding site have lower DAA than those with double/ multiple binding sites, as shown for CR1 and C4BP compared with smallpox inhibitor of complement enzymes and VCP (39) or CR1 and factor H compared with CCPH and VCP (33). This observation also holds true for RCP-1, which dissociated convertases more effectively than its 4-CCP domain subunits or homolog RCP-H.…”
Section: Discussionmentioning
confidence: 99%
“…Initial characterization of this protein showed that it has the ability to inhibit complement activation (Fodor et al, 1995). Later, its detailed functional characterization showed that like poxviral RCA proteins, it also has the ability to accelerate decay of the CP/LP C3 convertase and to a lesser extent the AP C3 convertases as well as inactivate C3b and C4b resulting in inhibition of the CP/LP as well as the AP (Singh et al, 2006). Besides, the domain requirement of this protein for complement inactivation was essentially similar to that of the poxviral RCA proteins (Singh et al, 2009;Reza et al, 2013).…”
Section: Gammaherpesvirusesmentioning
confidence: 99%
“…Armed with this information on DAF, we then analyzed the extent of conservation of residues in DAF and in other C3 convertase regulators determined by mutagenesis to be important, either for cofactor activity or for DAA (12,18,21,22,(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41). Whereas we found an absence of strict conservation of residues which distinguish the two functions, by focusing alignment on the sequence flanking the CCP2 and -3 junction where DAF function resides, we identified differences between those regulators that 1) mediate DAA and 2) mediate cofactor activity.…”
Section: Discussionmentioning
confidence: 99%